How to present to absolutely anyone : confident public speaking and presenting in every situation - Rhodes, Mark (Capstone a Wiley brand, 2019)
How to Present to Absolutely Anyone is the ultimate guide to successful public speaking. Presentations, talks, and speeches are unavoidable in school, work and even social occasions - but fear of public speaking is statistically more common than fear of death. Author Mark Rhodes once pretended he had crashed his car to avoid doing a presentation! Permanent avoidance will eventually hold you back, but mastering the art of the successful presentation can take you to new heights! This book shows you how Mark eventually learned to love public speaking: by setting himself up for a self-sustaining cycle of presentation success.